Peranan Pengendalian Internal Sebagai Alat Bantu Manajemen Dalam Pengamanan Pemberian Kredit Mikro - Kusuma, Dewi Puspa Wijaya; Hasibuan, David HM (Institut Bisnis dan Informatika Kesatuan, 2013)
Bank, as financial institutions in banking, is a unique and exciting company to be exploredfurther because the bank as intermediary media have an important role and more or less influencedthe development of a country's interconnected economy, especially in Indonesia. Given the bank'sunderstanding of itself as an institution that functions as a funding channel to the communitiesthat need, it iscertainly not free from two things likely happened to the bank itself, could lead to thepositive impact of increased interest earned from lending or risk of the debtor problematic.Evaluation conducted to determine whether internal controls are adequate conducted by thecompany and assist management in securing credit. Research on the author is in the PT. Bank XCluster Micro Business Unit (Central Branch) located in Bogor. PT. Bank X is a companyengaged in banking. Based on the results obtained from the authors note that the company'sinternal controls are carried out in the PT. Bank X is represented by the Cluster Manager isadequate. Control is inadequate because it was the clarity of separation of duties, creditauthorization, and appropriate documents. Internal control is performed by the Cluster Manager isupdated from time to time. The results of a study conducted by researchers showed that the internalcontrol carried out by PT. Bank X was instrumental in securing the provision of credit and internalcontrol systems are contained in the PT. Bank X has been inadequate. This can be seen from eachof the components that make up the internal controls at PT. Bank X. With the separation ofduties, imposed credit policy and authorization functions loans are already well underway. It isalso seen from the Internal Control Flowchart Questionnaire and that the company has met all fivecomponents of internal control system according to COSO. Credit system and its protection goeswell and there is evidence that in accordance with the loan documents.